Family relationships in Algerian society between traditional assets and technologicalmodernity (Numerus academy review, 2026)
Family relationships in Algerian society are categorized by simplicity, asrelationship between parents and children was symbolized by the character of mutual respect and appreciation, in addition to their contribution to the application andconsolidation of family values; however, these values have changed due to the new technological modernity, which is considered as double-edged weapon, seeing that itincreases closeness of people, raises the degree of their interaction and creates new virtual relationships. On the other hand, it constitutes a real danger to social and familyrelationships, as it leads to the creation of an intellectually and educationally discordantsociety.That's the change bears the factors of breaking with cultural traditions; in the lightof which, this results in changing the social value system of individuals, increases the desire and tendency for loneliness and isolation, and reduces, accordingly, opportunitiesfor realistic interaction and social dialogue within the same family.